Employment in distributive trade: Croatian experience and expectations - Drago Pupavac; Helga Pavlić Skender; Aleksandar Skendžić (Przedsiębiorczość Międzynarodowa, 2016)
In Croatia, distributive trade is one of the most important economic sectors. The direct contribution of distributive trade to GDP in Croatia was 9,6% of total GDP in 2013. Another important fact is that distributive trade is a labor intensiveindustry. In Croatia, where problems such as high rate of unemployment, public debt, unfavorable trade balance systematically and cautiously planned distributive trade  development plays an important role in the country's economy. It employs 205,849 people or 15,3% of the total labor force in Croatia. Economic crisis has diminished the importance of distributive trade in the creation of new jobs.Number of employees in this industry so decreased by 23.8 percent compared to 2008.  Therefore, the main purpose of this research is to examine the relationship between the Gross Domestic Product(GDP), number of total employment and the number of distributive trade employees of the Republic of Croatia for periods 2000-2014. The methods of correlation and regression analyses are used to determine the possible contribution of trade sector as an economic activity in solution of the unemployment problem in Croatia by 2030. Data analysis and numerical calculations are performed using Statistical software.